2020
DOI: 10.2196/21659
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence–Powered Smartphone App to Facilitate Medication Adherence: Protocol for a Human Factors Design Study

Abstract: Background Medication Guides consisting of crucial interactions and side effects are extensive and complex. Due to the exhaustive information, patients do not retain the necessary medication information, which can result in hospitalizations and medication nonadherence. A gap exists in understanding patients’ cognition of managing complex medication information. However, advancements in technology and artificial intelligence (AI) allow us to understand patient cognitive processes to design an app to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For example, patients are traditionally required to commit to a physician’s consultative appointment that could be relatively inflexible because of a long list of patients, and one could be forced to skip the consultation because of a conflict in their schedule. AI confers the benefit of information collection and dissemination beyond the constraints of time and place, which have been shown to improve medication adherence through an AI-based smartphone app [ 51 ] and diet and exercise adherence through an AI-based virtual health assistant [ 52 ]. Our findings also demonstrated that AI is valued for its potential to speed up health care processes such as diagnosis, waiting time, communication with care teams, decisional support, and other routine tasks (eg, progress monitoring) that can be automated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients are traditionally required to commit to a physician’s consultative appointment that could be relatively inflexible because of a long list of patients, and one could be forced to skip the consultation because of a conflict in their schedule. AI confers the benefit of information collection and dissemination beyond the constraints of time and place, which have been shown to improve medication adherence through an AI-based smartphone app [ 51 ] and diet and exercise adherence through an AI-based virtual health assistant [ 52 ]. Our findings also demonstrated that AI is valued for its potential to speed up health care processes such as diagnosis, waiting time, communication with care teams, decisional support, and other routine tasks (eg, progress monitoring) that can be automated.…”
Section: Discussionmentioning
confidence: 99%
“…Future intuitive interfaces taking consideration of heuristics and artificial intelligence methods may fill in the gap. [56][57][58] Future studies may evaluate the coverage of the 27 if-then logic heuristics for their usefulness in system design. Developing a metric to quantify the outcome of these heuristics in system design may be necessary.…”
Section: Implications For Health It System Designmentioning
confidence: 99%
“…Integrating pharmacy claims data with more complete data sources, such as clinical and health outcomes, would provide information on the clinical indication for each medication and reasons for medication changes or cessation [ 39 , 40 ]. This integration could also be used to establish the association between gaps or lapses in medication refills and adverse health outcomes and healthcare resource use.…”
Section: Real-world Challengesmentioning
confidence: 99%